Capturing, the experiences of undergraduate student nurses undertaking a pre-registration nursing degree course using an adapted experience based co-design approach. (June 2023) - Pollitt, Sam; Gurbutt, Dawne; Harrison, Nigel; Duckworth, Jean E.
Abstract: Background: The quality of student experience in higher education plays an increasingly important role in attracting and retaining pre-registration nurses. Identifying and understanding the students' experiences of their course is a necessary step in the move towards improving the student experience. Experience Based Co-design (EBCD) is successfully established as an effective process for improving patient experience in a health care setting. This study presents the use of EBCD outside of healthcare, specifically in a higher education setting. Objectives: To capture, explore and understand the experiences of students' undertaking a pre-registration (adult) nursing course, and co-design potential improvements for future experiences through the application of an EBCD approach. Methods: An adapted EBCD approach was utilised for gaining insight into what shapes students' experience of the nursing course and to collaboratively produce priority recommendations for course improvement. Semi-structured interviews, emotional touchpoint mapping and co-design events were conducted with undergraduate nursing students (n = 22) and staff stakeholders in a pre-registration (adult) nursing course (n = 19). Findings were analysed using the 'Six phases of thematic analysis' (Braun & Clarke, 2006). Results: Students had varied experiences on the nursing course, both positive and negative, particularly with student support. Three priority recommendations for course improvement were identified from the findings including: facilitating and supporting student development of independent study skills, enhancing student support in the clinical practice placement environment and clarifying and enhancing the role of the academic advisor. Conclusions: Findings from this study highlight areas for improvement on a pre-registration nursing course that could impact future students' experience. Furthermore, this study appears to be the first documented as using EBCD in a higher education setting with the focus on students, that enabled students and staff stakeholders in the nursing course to co-design priority recommendations for course improvement.